678 Addition of a single bacteria facilitates anti-tumor immunity and long-term survival in colorectal cancer. (10th December 2020) - Overacre-Delgoffe, Abigail; Cillo, Anthony; Bumgarner, Hannah; Burr, Ansen; Tometich, Justin; Bhattacharjee, Amrita; Bruno, Tullia; Vignali, Dario; Hand, Timothy
Abstract : Background: Colorectal cancer remains one of the most common and deadliest cancers worldwide and effective therapies are lacking. While immunotherapy has revolutionized treatment for many cancers, the overwhelming majority of colorectal cancer patients are non-responsive and the 5-year survival rate for advanced disease is <20%. Immunotherapeutic response has been associated with select members of the microbiome in melanoma; however, the potential benefit in colorectal cancer and the underlying mechanisms remain unclear. We sought to determine how specific members of the intestinal microbiome affect anti-tumor immunity in colorectal cancer (CRC) in hopes of discovering novel treatments and revealing potential hurdles to current therapeutic response in CRC patients. Methods: We utilized a carcinogen-induced mouse model of CRC and colonized half of the tumor-bearing mice with Helicobacter hepaticus (Hhep) 7 weeks post AOM. Tumor number was assessed 12 weeks post AOM. We isolated lymphocytes from the lamina propria, colonic epithelium, mesenteric lymph nodes, and tumor(s) to track the spatial and transcriptional Hhep-specific and endogenous immune responses during tumor progression through 5' single cell RNAseq, flow cytometry, and immunofluorescence. In addition, we utilized 16S sequencing and FISH to track Hhep colonization, location within the colon, and its impact on the surrounding microbiome. Results: We have found that rational modification of the microbiome of colon tumor-bearing mice through addition of a single bacteria, Hhep, led to tumor control or clearance and a significant survival advantage. Colonization led to the expansion of the lymphatic network and development of numerous peri- or intra-tumoral tertiary lymphoid structures (TLS) composed of Hhep-specific CD4 T follicular helper cells (TFH) as well as the bacteria itself. This led to an overall 'heating' of the tumor, wherein we saw an increase of CD4 T cell infiltration to the tumor core as well as an increase in CD103+ type 1 DC (cDC1) recruitment through increased chemokines such as CCL5 and XCL1. Hhep-specific TFH were both necessary and sufficient to drive TLS formation, increased immune invasion, and anti-tumor immunity. Conclusions: We have shown that addition of a single bacteria, Hhep, leads to a reduction in CRC tumor burden or clearance through lymphatic expansion, TLS formation, and remodeling of the tumor microenvironment, and that Hhep-specific T cells are required for tumor control. These studies suggest that rational modification of the microbiome and microbiome-specific T cells can positively impact anti-tumor immunity and may represent a unique immunotherapeutic target to turn resistant tumors into responsive tumors.